Quantifying the impacts of volume-based procurement policy on spatial accessibility of antidepressants via generic substitution: A four-city cohort study using drug sales data - Aoming Xue; Qingyuan Xue; Jiahong Fu; Keye Fan; Jiale Zhang; Peiyan Cai; Yuanyuan Kuang; Yingsong Chen; Jifang Zhou; Bin Jiang (PLoS ONE, 2025)
Objective To assess the spatial accessibility and inequality of antidepressants and its correlation with VBP (Volume-based procurement) policy using procurement data from four representative Chinese cities between 2018 and 2020. Methods The least-cost-path algorithm was employed to calculate travel time from each population point to the nearest medical institution. Gini coefficient and Theil index were utilized to measure accessibility and inequality. OLS (Ordinary Least Squares) and mediation analysis were used to investigate potential statistical relationships. Results Under the influence of the VBP policy, we observed varying degrees of growth in the procurement volumes of two antidepressants across different cities (Escitalopram: Beijing 30.3%, Shanghai 26.2%, Ningbo 37.4%, Harbin 25.7%; Paroxetine: Beijing 28.2%, Shanghai 1.2%, Ningbo 50.2%, Harbin 590.5%). The increase in the procurement volumes of antidepressants across cities was primarily driven by generic drugs (Escitalopram: Beijing 159.8%, Shanghai 75.0%, Ningbo 146.4%, Harbin 146.3%; Paroxetine: Beijing 67.3%, Shanghai 4.9%, Ningbo 58.0%, Harbin 15,758.3%). In the results on spatial inequality, we observed annual improvements across all cities, with more pronounced progress in economically underdeveloped regions (Escitalopram: Gini in Harbin decreased by 10.6%; Paroxetine: Gini in Harbin decreased by 32.6%). In Beijing, the substitution of generic escitalopram was found to be a partial mediating factor in the improvement of spatial inequality (ACME = -0.00, p-value = 0.01; ADE = -0.00, p-value = 0.02). In Harbin, the substitution of generic paroxetine was identified as a complete mediating factor for spatial inequality (ACME = -0.04, p-value = 0.01; ADE = 0.01, p-value = 0.14). Conclusions This study found that the spatial accessibility and inequality of antidepressant medications gradually improved under the influence of the VBP policy. These improvements can be partially attributed to the substitution of generic drugs.